Ig Light Chain Precedes Heavy Chain Gene Rearrangement during Development of B Cells in Swine - Sinkora, Marek; Sinkorova, Jana; Stepanova, Katerina (The Journal of immunology, 2017)
The current mammalian paradigm states that 1) rearrangements in the IgH locus precede those in IgL loci, 2) IgLλ genes rearrange only when IgLκ genes are consumed, and 3) the surrogate L chain is necessary for selection of productive IgH gene rearrangements. We show in swine that IgL rearrangements precede IgH gene rearrangements, resulting in the expression of naked IgL on a surface of precursor B cells. Findings also suggest that there is no dependency on the surrogate L chain, and thus the authentic IgL proteins may be used for selection of the IgH repertoire. Although rearrangement starts with IgLκ genes, it is rapidly replaced by IgLλ rearrangement. Fast replacement is characterized by occurrence of IgLλ(lo)IgLκ(lo) dual-expressing precursors in which IgLκ expression is a remnant of a previous translation. Most IgLκ(+) B cells are then generated later, indicating that there are two waves of IgLκ synthesis in different developmental stages with IgLλ gene rearrangements in between. In the absence of stromal cells, the stepwise order of rearrangements is blocked so that IgLλ gene rearrangements predominate in early B cell development. To our knowledge, this is the first evidence that some mammals can use an inverted order of Ig loci rearrangement. Moreover, a situation in which the generation of BCR-bearing IgLκ is delayed until after IgLλ becomes the dominant isotype may help explain the extreme deviations in the IgLκ/IgLλ ratios among mammals.
Keywords: Immunoglobulin kappa-Chains; přestavba genů pro lehké řetězce B-lymfocytů; Receptors, Antigen, B-Cell; těžké řetězce imunoglobulinů; lehké řetězce imunoglobulinů; zvířata; geny pro imunoglobuliny; Gene Rearrangement, B-Lymphocyte, Light Chain; receptory antigenů B-buněk; Immunoglobulin Light Chains; Genes, Immunoglobulin; B-Lymphocytes; přestavba genů pro těžké řetězce B-lymfocytů; Swine; prasata; Immunoglobulin Heavy Chains; B-lymfocyty; Animals; Gene Rearrangement, B-Lymphocyte, Heavy Chain; imunoglobuliny - kappa-řetězce